ЗОВНІШНЬОПОЛІТИЧНІ ФАКТОРИ ДЕРЖАВОТВОРЕННЯ УКРАЇНЦІВ ТА ІНШИХ НАРОДІВ ЦЕНТРАЛЬНО-СХІДНОЇ ЄВРОПИ (1917-1920 рр.) (Zaporizhzhia Historical Review, 2021)
The article deals with the comparative analysis of the external political conditions in which the idea of the independent state was revived by the Ukrainians and some other peoples of Central-Eastern Europe. The scolar proves that the mentioned conditions were similar for the Ukrainians, the Poles, the Checks, the Estonians, the Latvians and the Lithuanians. The negative role was played by the political theories of Ukrainian elite whose ideal was deeply rooted into the ideas of socialism and federalism.